Information System for Calculating Medical Record Personnel in the Industrial Revolution Era 4.0 - Al hadri, Cecilia Farrona; Sunandar, Ahmad (Politeknik Negeri Madiun, 2021)
Medical recorders and health information are some of the health workers who are included in the